PENGUATAN TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN ORGANISASI PEMUDA PANCASILA SEBAGAI UPAYA GOOD GOVERNANCE - Lilis Setyowati; Ngurah Pandji Mertha Agung Durya; Ririh Dian Pratiwi; Dian Festiana Hadi Saputro; Yulita Setiawanta (SWADIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2026)
The application of good governance principles in community organizations is crucial, ensuring transparency and accountability. The Pancasila Youth Organization, as a youth organization, plays a vital role in social development, but still faces challenges in administrative and financial management. This community service activity aims to strengthen transparency and accountability in the management of the Pancasila Youth Organization in Semarang City, as part of an effort to implement good governance principles. The method used was a participatory approach by providing outreach, training, and guidance to the organization's administrators. The activity results showed increased understanding among administrators of transparency, accountability, and effective organizational governance, as well as improvements in the organization's administrative and financial systems. This activity helped foster more transparent and accountable organizational governance, thereby supporting the sustainable role of youth organizations in community social development.Penerapan prinsip good governance dalam organisasi kemasyarakatan sangat penting melalui tata kelola yang transparan dan akuntabel. Organisasi Pemuda Pancasila, sebagai organisasi kepemudaan, memiliki peran penting dalam pembangunan sosial, namun masih menghadapi kendala dalam pengelolaan administrasi dan keuangan. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memperkuat transparansi dan akuntabilitas dalam pengelolaan organisasi Pemuda Pancasila di Kota Semarang, sebagai bagian dari upaya menerapkan prinsip good governance. Metode yang digunakan adalah pendekatan partisipatif dengan cara memberi sosialisasi, pelatihan, dan bimbingan kepada pengurus organisasi. Hasil kegiatan menunjukkan adanya peningkatan pemahaman pengurus mengenai transparansi, akuntabilitas, serta tata kelola organisasi yang baik, serta perbaikan dalam sistem administrasi dan keuangan organisasi. Kegiatan ini berkontribusi dalam mendorong terwujudnya tata kelola organisasi yang lebih transparan dan akuntabel, sehingga mendukung keberlanjutan peran organisasi kepemudaan dalam pembangunan sosial masyarakat